Transformasi Pendidikan Agama Islam Di Era Society 5.0: Strategi Penguatan Guru Madrasah Ibtidaiyah - Anas Sofyan (Jurnal Pendidikan Islam, 2026)
This study aims to analyze the transformation of I slamic Religious Education (PAI) in the Society 5.0 era and the strategies for strengthening Madrasah Ibtidaiyah teachers in responding to technological advancements and changing student characteristics. This research employs a qualitative approach with a case study method, utilizing data collection techniques such as interviews, observations, and documentation. The findings reveal that the transformation of PAI is characterized by a shift from conventional teaching methods to digital-based learning that is interactive, contextual, and humanistic. The use of digital media, such as instructional videos, Qur'an applications, and interactive platforms, has been proven to enhance student engagement, motivation, and understanding. However, this transformation also faces several challenges, including limited digital literacy among teachers, lack of continuous professional training, and inadequate infrastructure. Therefore, comprehensive strategies are needed to strengthen teachers, including improving digital competencies, enhancing technology-based pedagogical skills, and integrating Islamic values into the learning process. Teachers play a strategic role as learning facilitators and value guardians in ensuring that technology use remains aligned with the principles of Islamic education. Thus, the transformation of PAI in the Society 5.0 era is expected to create innovative and relevant learning while contributing to the development of students’ character, making them morally grounded and adaptable to technological changes.